Tensile properties of wood sawdust fibre reinforced epoxy composites - Siregar, Januar Parlaungan; Dewi, Rozanna; Imran, Al Ichlas (INTI Publishing Network, 2023)
This study conducts an extensive examination of the tensile properties of epoxy resin composites strengthened with wood sawdust fiber. It emphasizes the potential of these composites as a sustainable and cost-effective substitute in the automotive industry. Sawdust particles with a mesh size of 100 and weights of 10%, 20%, and 30% are mixed with epoxy resin in this experiment so that tensile stress and tensile modulus under load can be observed in detail. The fabrication process involved the manual lay-up of tensile specimens. The results indicate that the tensile properties of composites containing 20% sawdust are an unexpected 30% superior to those comprising 10% filler loading. In contrast, micrograph tensile fracture examinations unveiled the presence of agglomeration and air bubble, factors that compromised the accuracy of the findings. The results demonstrate the critical nature of optimizing the sawdust content to attain the optimal equilibrium in the mechanical properties of composites. It is recommended that future applications implement additional microstructural control measures and refine the fabrication process to enhance precision and dependability.